Protection of the Right to Elderly Health Insurance at the Semarang City Nursing Home - Lina Purnamasari; Y. Budi Sarwo; Daniel Budi Wibowo (Universitas Katolik Soegijapranata Semarang, 2020)
Semarang has the second largest elderly in Indonesia. The elderly are vulnerable to illness and have the right to health insurance held by the Government, in this case, membership of the National Health Insurance (JKN) or Semarang Regional Health Insurance. This study aims to determine the protection of health insurance rights of neglected or poor elderly in nursing homes in Semarang.The design study was a socio-legal approach. Data was taken through literature and field studies, through an interview with a representative of the Semarang Health Department, Semarang Social Department, BPJS Semarang, head/caretaker, and elderly of three nursing home in Semarang. Data is analyzed qualitatively. This study found that there was no specific regulation regarding the protection of health insurance rights of the elderly in nursing homes. Elderly received routine health care in the three nursing homes, but only 50%, 17%, and 8% elderly were registered as JKN membership and none were registered in Semarang Regional Health Insurance. Many elderly have not been registered because they do not have Family Cards and Identity Cards, limitations of nursing home staffs managing registration, lack of roles and coordination of Local Government institutions in providing health insurance for neglected elderly.